2017
DOI: 10.1515/folmed-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes in Experimental Rat Model of Abdominal Compartment Syndrome

Abstract: Background: Increased intra-abdominal pressure (IAP) causes tissue ischemia, subsequent hypoxia, and impairment of normal tissue metabolism. Elevation of IAP above 20 mmHg leads to progression of abdominal compartment syndrome (ACS) that is associated with organ dysfunction or failure not previously manifested. Aim: To evaluate the eff ects of diff erent grades and time of exposure to IAP on biochemical parameters and oxidative stress in organs aff ected by ischemia using previously developed rat model. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Wang et al found [31] that flavonol glycosides which are in high concentrations in Inula racemosa altered cellular morphology, and cytokines and AST were returned to near normal level in hepatic I/R injury. Ardasheva et al elevated the intra-abdominal pressure (IAP) above 20 mmHg which led [32] to progression of abdominal compartment syndrome that is associated with organ dysfunction or failure and elevated activities of AST found in some of the experimental groups than control ones of animals not subjected to increased IAP and time frame tested for liver. Zazueta et al found [33] that citicoline CDPcholine reduced ASTl in blood samples from reperfused rats in I/R rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found [31] that flavonol glycosides which are in high concentrations in Inula racemosa altered cellular morphology, and cytokines and AST were returned to near normal level in hepatic I/R injury. Ardasheva et al elevated the intra-abdominal pressure (IAP) above 20 mmHg which led [32] to progression of abdominal compartment syndrome that is associated with organ dysfunction or failure and elevated activities of AST found in some of the experimental groups than control ones of animals not subjected to increased IAP and time frame tested for liver. Zazueta et al found [33] that citicoline CDPcholine reduced ASTl in blood samples from reperfused rats in I/R rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of serum or urinary biomarkers was performed both on experimental and human subjects to assess the possibility of an earlier diagnosis of intra-abdominal hypertension or abdominal compartment syndrome. Several biomarkers were examined: kidney dysfunction (BUN and creatinine), intestinal damage (D-lactate [77,78], D-dimer [79], Intestinal Fatty Acid Binding Protein, and I-FABP [80,81]), aspartate aminotransferase [80], oxidative stress biomarkers such as glutathione [82,83], superoxide dismutase isoenzymes [84], and fatty acid ethyl esters [85].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…D-Lactate can be overproduced by microbiota under specific circumstances like short bowel syndrome and jejunoileal bypass surgery further supported when a patient takes a meal with high sugar content [ 51 , 52 ]. Abdominal compartment syndrome, a multiorgan failure associated with fluid accumulation within the peritoneal and retroperitoneal spaces, is another risk factor for increased D-lactate concentration in blood [ 53 ]. The presence of D-lactate can follow poisoning to heavy metals despite the exact mechanism remaining unknown.…”
Section: Poisoning By D-lactate and D-lactic Acidosismentioning
confidence: 99%